2016
DOI: 10.1016/j.rbre.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Mild and moderate Mannose Binding Lectin deficiency are associated with systemic lupus erythematosus and lupus nephritis in Brazilian patients

Abstract: This study shows that an association between MBL deficiency and SLE does exist in the Brazilian population. We also found an association between MBL deficiency and lupus nephritis. These findings support the hypothesis that MBL deficiency contributes to the development of SLE and lupus nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…From a physiological and clinical point of view, the optimal cut-off value for low p-MBL levels still has to be determined: either across diseases or solely concerning RPL patients. In Danish laboratories, a p-MBL level ≤500 µg/l is defined as insufficient, and this is in agreement with the cut-off value used in previous studies investigating the impact of p-MBL levels in diseases such as severe acute respiratory syndrome coronavirus infection, chronic obstructive lung disease, systemic lupus erythematosus (SLE) and lupus nephritis ( Ip et al , 2005 ; Eagan et al , 2010 ; Albert et al , 2012 ; Perazzio et al , 2016 ). The optimal cut-off value probably varies between diseases but may also depend on the applied method of measurement.…”
Section: Discussionsupporting
confidence: 83%
“…From a physiological and clinical point of view, the optimal cut-off value for low p-MBL levels still has to be determined: either across diseases or solely concerning RPL patients. In Danish laboratories, a p-MBL level ≤500 µg/l is defined as insufficient, and this is in agreement with the cut-off value used in previous studies investigating the impact of p-MBL levels in diseases such as severe acute respiratory syndrome coronavirus infection, chronic obstructive lung disease, systemic lupus erythematosus (SLE) and lupus nephritis ( Ip et al , 2005 ; Eagan et al , 2010 ; Albert et al , 2012 ; Perazzio et al , 2016 ). The optimal cut-off value probably varies between diseases but may also depend on the applied method of measurement.…”
Section: Discussionsupporting
confidence: 83%
“…In 2001, Saevarsdottir et al [34] reported that patients with rheumatoid arthritis and low MBL levels had more serious joint damage and worse response to treatment. In 2011, Brazilian researchers found that low to moderate MBL deficiency was associated with a high incidence of lupus nephritis [35]. In recent years, Guo et al [36] confirmed that the symptoms of hematuria and infection were significantly worse in patients with low MBL levels than in those without MBL deficiency in a sample of 749 patients with IgA nephropathy; in an adjusted analysis, MBL deficiency was an independent risk factor for renal deterioration in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…MBL manifests itself with immunoglobulin (Ig) G deposits in the kidney biopsy materials of patients with lupus nephropathy, membrane-proliferative glomerulonephritis, anti-glomerular basement membrane nephritis, focal segmental glomerulosclerosis, and IgA nephropathy (7) . It has been suggested that a MBL genetic defect can be related to the development of SLE; lower MBL levels serve as a risk factor in terms of SLE development (18,19) . In membranous nephropathy (MN) and Henoch-Schönlein Purpura nephritis, complement activation through the lectin pathway may play a role in the development of advanced glomerular injuries (20)(21)(22) .…”
Section: Discussionmentioning
confidence: 99%